2003
DOI: 10.1145/966049.777397
|View full text |Cite
|
Sign up to set email alerts
|

Extending sized type with collection analysis

Abstract: Many program optimizations and analyses, such as arraybounds checking, termination analysis, depend on knowing the size of a function's input and output. However, size information can be difficult to compute. Firstly, accurate size computation requires detecting a size relation between different inputs of a function. Secondly, size information may also be contained inside a collection (data structure with multiple elements). In this paper, we introduce some techniques to derive universal and existential size p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This capability is particularly important for analyses that handle dynamically allocated data structures where the number of objects is statically unbounded (Møller and Schwartzbach, 2001;Yorsh et al, 2004;Sagiv et al, 2002). Recently, these approaches were extended to handle the combinations of the constraints representing data structure contents and constraints representing numerical properties of data structures (Rugina, 2004;Chin et al, 2003). Our result provides a systematic mechanism for building precise and predictable versions of such analyses.…”
Section: Related Workmentioning
confidence: 99%
“…This capability is particularly important for analyses that handle dynamically allocated data structures where the number of objects is statically unbounded (Møller and Schwartzbach, 2001;Yorsh et al, 2004;Sagiv et al, 2002). Recently, these approaches were extended to handle the combinations of the constraints representing data structure contents and constraints representing numerical properties of data structures (Rugina, 2004;Chin et al, 2003). Our result provides a systematic mechanism for building precise and predictable versions of such analyses.…”
Section: Related Workmentioning
confidence: 99%
“…Note that the unwinding only contains functions that are involved in the counterexample, that is, main and H (as well as F and G beyond depth 2) are sliced out. 7 We discuss the key properties of unwinding. First, because d is simply typable, d…”
Section: Unwindingmentioning
confidence: 99%
“…Chin et al [6,7] have also suggested a constraint unrolling approach with the Omega test [33] as the backend solver. These approaches use neither candidate types nor a fixed-point type inference routine, but they resemble the refinement phase of our work in that they also reduce the inference problem to finding a solution to a set of first-order logic constraints.…”
Section: Inferring Dependent Typesmentioning
confidence: 99%
“…The rest of the rules remain the same, just replacing ⊢ with ⊢ 1 , and ⊢∧ with ⊢ 1 ∧ . We eliminate any intersection of base types via the equivalence {u:B | θ1} ∧ {u:B | θ2} = 7 The implementation performs additional optimizations that can further reduce the size of the unwinding by slicing out more irrelevant parts.…”
Section: Linear Intersection Typesmentioning
confidence: 99%